Effects of pomegranate peel and olive pomace supplementation on reproduction and oxidative status of rabbit doe. Issue 3 (27th July 2021) - Bakeer, Manal; Abdelrahman, Hisham; Khalil, Karim
Abstract: The current study aimed to investigate the effects of pomegranate peel and olive pomace supplementation on the reproductive hormones, antioxidative status, reproductive capacity and maternal behaviour of rabbit does. Forty does were used for the experiments. The animals were randomly assigned to four groups of ten does. One group was fed on the control diet and was considered the control group (C). The second group was supplemented with 4.5% pomegranate peel in their diet (P), the third group was supplemented with 10% olive pomace in their diet (O), and the fourth group was supplemented with a mixture of pomegranate peel and olive pomace (PO). Compared with the control does, group P showed significantly increased serum levels of gonadotropic hormones and oestradiol‐17β two hours after mating, on the 20th day of lactation and after weaning; significantly increased progesterone levels at mid‐pregnancy; and significantly increased in prolactin levels on the 10th day of lactation. Additionally, the results revealed significant increases in total DNA, protein concentration, litter size, milk yield and nest traits of groups P and PO. In conclusion, pomegranate peel supplementation improves the reproductive performance of does and increases their antioxidant parameters.